2011
DOI: 10.1371/journal.pone.0021811
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3C Inhibits Tumor Growth and Increases the Anticancer Activity of Bortezomib in a Murine Model of Human Multiple Myeloma

Abstract: Galectin-3 is a human lectin involved in many cellular processes including differentiation, apoptosis, angiogenesis, neoplastic transformation, and metastasis. We evaluated galectin-3C, an N-terminally truncated form of galectin-3 that is thought to act as a dominant negative inhibitor, as a potential treatment for multiple myeloma (MM). Galectin-3 was expressed at varying levels by all 9 human MM cell lines tested. In vitro galectin-3C exhibited modest anti-proliferative effects on MM cells and inhibited chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 70 publications
5
35
0
5
Order By: Relevance
“…The results suggest that galectin-3 may act as a binding partner of platelet collagen receptors and, interestingly, imply that the binding is dependent on carbohydrate binding mediated by CRD and by homologous or heterologous protein-protein binding mediated by the collagen-like domain. Our results showing that Gal-3C prevented platelet-induced COX-2 overexpression in cancer cells also suggest that this could be a mechanism of its anticancer activity, as demonstrated in animal models (John et al, 2003;Mirandola et al, 2011). The contribution of PDGF, released by activated platelets, to the induction of COX-2 in HT29 cells was disclosed by blocking PDGFR activation with imatinib (Buchdunger et al, 2002) or by using a PDGF-neutralizing antibody.…”
Section: Discussionsupporting
confidence: 71%
“…The results suggest that galectin-3 may act as a binding partner of platelet collagen receptors and, interestingly, imply that the binding is dependent on carbohydrate binding mediated by CRD and by homologous or heterologous protein-protein binding mediated by the collagen-like domain. Our results showing that Gal-3C prevented platelet-induced COX-2 overexpression in cancer cells also suggest that this could be a mechanism of its anticancer activity, as demonstrated in animal models (John et al, 2003;Mirandola et al, 2011). The contribution of PDGF, released by activated platelets, to the induction of COX-2 in HT29 cells was disclosed by blocking PDGFR activation with imatinib (Buchdunger et al, 2002) or by using a PDGF-neutralizing antibody.…”
Section: Discussionsupporting
confidence: 71%
“…This truncated version fails to support neutrophil adhesion [29] and fails to induce migration and capillary tubule formation in endothelial cells in vitro and angiogenesis in vivo [7]. Conversely, it inhibited tumor growth and metastasis in the orthotopic nude mouse model of human breast cancer and also inhibited tumor growth and increased the anticancer activity of Bortezomib in a murine model of human multiple myeloma [30]. Surprisingly, our data showed that G111-250, a CRD fragment similar to Gal3C, followed transport pathways different from those of the full-length protein.…”
Section: Discussionmentioning
confidence: 99%
“…21 Tumor growth was monitored by U266-specific IgE protein secretion in mouse serum. 22,23 While IL-2-expanded L-chainspecific CD8 C T cells can lyse the tumor cells very well in vitro, 17 these T cells only temporarily inhibited tumor cell growth in vivo (Fig. 1A).…”
Section: In Vivo Antitumor Effects Of Adoptively Transferred Id L-chamentioning
confidence: 99%